Evaluation of sarcopenia in patients with hyperthyroidism - Tufan , Aslı; Engin, Ebru; Elbasan, Onur; Senturk Durmus, Nurdan; Can, Busra; Ilgin, Can; Can, Bulent (Progress in Nutrition, 2022)
Background and aim: Sarcopenia is a generalized skeletal muscle disease and thyroid hormones have regulatory effects on skeletal muscle metabolism. This study aims to evaluate the association between hyperthyroidism and sarcopenia.Methods: Thirteen patients with overt hyperthyroidism (OH), 13 patients with subclinical hyperthyroidism (SH) and 30 healthy volunteers were included. OH was defined as serum thyroid-stimulating hormone (TSH) 1.12 ng/dL and/or free T3 (fT3) >4.37 ng/L; while SH was defined as TSH